The ‘black waters’ of Malaysia: tracking water quality from the peat swamp forest to the sea - Irvine, Kim; Vermette, Stephen; Firuza Begham Mustafa, (Universiti Kebangsaan Malaysia, 2013)
Longitudinal water quality trends were assessed in the Tengi River system, Selangor, Malaysia, as the water moved from a peat swamp forest, through different agricultural land uses and finally through a town and then to the Straits of Malacca. Water draining from the peat swamp forest was dark in color due to its organic content and low in dissolved oxygen, pH, E. coli, calcium, nitrate and ammonia. The normal diurnal pattern for water temperature was observed for the peat swamp forest drainage, but there was no clear diurnal pattern evident in the dissolved oxygen data. The E. coli levels increased monotonically from the peat swamp forest waters (0 colonies/100 mL) through the agricultural areas (100-2000 colonies/100 mL) and town (7100 colonies/100 mL) and similarly pH increased along the same continuum. Dissolved oxygen increased from the peat swamp forest through the agricultural areas, but was lower in the town-impacted reach of the Tengi River.